Safranal Attenuates Excitotoxin-Induced Oxidative OLN-93 Cells Injury - Alavi, Mohaddeseh Sadat; Fanoudi, Sahar; Fard, Ameneh Veisi; Soukhtanloo, Mohammad; Hosseini, Mahmoud; Barzegar, Hanif; Sadeghnia, Hamid R. (Drug Research, 2019)
Objectives Researches have been shown that glutamic acid (GA) or quinolinic acid (QA) can play role in neuroinflammatory and demyelinating diseases including multiple sclerosis (MS), mainly via oligodendrocytes activation and extreme free radicals generation. Recent studies have demonstrated that safranal, an active constituent of Crocus sativus, has several pharmacological effects such as antioxidant, anti-inflammatory and neuroprotective properties. Since there is no data about the impact of safranal on MS, this study was designed to investigate the protective effect of safranal on OLN-93 oligodendrocytes injury induced by GA or QA.Materials and Methods At first, the potential toxic effect of safranal on OLN-93 viability was evaluated. Also, the cells were pretreated with safranal (0.1, 1, 10, 50, 100 and 200 μM) for 2 h and then subjected to GA (16 mM) or QA (8 mM) toxicity for 24 h, in which the same treatments were applied. The cell viability and parameters of redox status such as the levels of intracellular reactive oxygen species (ROS) and lipid peroxidation were measured.Results Safranal at concentration ranges of 1–800 μM had no toxic effect on cell viability (p>0.05). Treatment with safranal significantly increased cell viability following GA or QA insults at concentrations higher than 1 μM (p<0.01). The cytoprotective potential of safranal was also accompanied by decreased ROS accumulation (p<0.001) and malondialdehyde level (p<0.001) following GA or QA insults.Conclusion The data suggests that safranal exhibits oligoprotection potential by means of inhibiting oxidative stress parameters.
Keywords: quinolinic acid; glutamic acid; safranal; oln-93 cells; gliotoxicity